Lectins from Eichornia crassipens and Lemna minor may be involved in Vibrio Cholerae El Tor adhesion - Córdoba-Aguilar, E; Coutiño-Rodríguez, R; Giles-Ríos, H; Hernández-Cruz, P; Mosqueda-Aguilar, A; Ríos-Cortés, P; Montero, H (Epidemiologie, mikrobiologie, imunologie, 2018)
Vibrio cholerae (Vc) has been isolated from roots of aquatic plants during epidemic or interepidemic periods. It has been suggested that the lectins from the roots of aquatic plants play a role as reservoirs of Vc. In this paper, we evaluated the activity of lectins from Lemna minor and Eichornia crassipens plants as potential mediators of the Vc strain El Tor (Vct). We found that Lemna minor extract showed high specificity towards blood groups O and B. Eichornia crassipens extract showed high specificity towards blood group A and O. Sugar competition experiments demonstrated that Lemna minor extract showed a high recognition to Neu5Ac (acid N acetyl neuraminic or sialic acid) and GlcNAc (N-acetyl D glucoseamine) in group B; and GlcNAc in group O. Eichornia crassipens, the recognition was that of GalNAc (N-acetyl-D-galactoseamine) and GlcNAc in group O; and Fuc (L-Fucose) and GlcNAc in group A. Lemna minor and Eichornia crassipens protein extracts (p-ext) increased Vct proliferation and protected to the red cells group O against the hemolytic activity of Vct. Both p-exts did not show any statistical significance on agglutination to Vct when compared to the results from phosphate buffer. According to the results, lectins present in roots may be involved in the proliferation and survival of Vct.
Keywords: lektiny; Lectins; Vibrio cholerae; Lemna minor; lidé; Araceae; Pontederiaceae; Humans